An empirical study on the influencing factors of community music participation of elderly groups in Chengdu city - Wang, Funan; Khatibi, Abdol Ali; Tham, Jacquline (Edelweiss Applied Science and Technology, 2025)
As aging continues to deepen in Chengdu, community music activities, as an important vehicle for promoting the psychological health and social connection of older adults, and their influencing factors have become the focus of healthy aging research. Based on Maslow’s hierarchy of needs theory and social-ecological system theory, this study conducted a questionnaire survey on a random sample of 480 older adults to systematically analyze the influence of individual needs, community environment, and social support on community music participation. The study found that: (1) demand-driven stratification: physiological needs and safety needs are the main driving forces for participation, while respect and self-actualization needs are seriously insufficient, leading to shallow participation behavior; (2) imbalance of environmental resources: the accessibility of community facilities, diversity of activities, and professional guidance are notably insufficient, especially in remote suburban communities; (3) fragile support system: family support is the core driving force, but the sustainability of activities is constrained by gaps in government funding and corporate sponsorship. The study proposes a synergistic path of “demand-environment-resource” optimization: activating high-level demand through layered activity design, breaking resource constraints through policy innovation and digital empowerment, and promoting the transformation of community music from “entertainment” to “value co-creation.” The theoretical value of this study is to build a localized framework for explaining cultural participation of the elderly and to provide a practical basis for decision-making on the construction of an “all-age friendly community” and the inheritance of NGT in Chengdu.